2019
DOI: 10.1002/wer.1035
|View full text |Cite
|
Sign up to set email alerts
|

A pilot‐scale deep bed denitrification filter for secondary effluent treatment using sodium acetate as external carbon

Abstract: A pilot-scale quartz sand deep bed denitrification filter (DBDF) using sodium acetate as the additional carbon source was implemented to treat secondary effluent, with a high nitrate nitrogen (NO 3 -N) concentration and low C/N ratio, from an urban municipal water resource recovery facility. By the 18th day, results showed that the removal efficiency of NO 3 -N and the chemical oxygen demand (COD) were stable at above 85% and 70%, respectively. When the filter layer depth was set to 1,600 mm and the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…DB is considered as a tertiary technology for further purifying nitrate-rich wastewater and has been widely applied in full-scale WWTPs. 30 In addition to microorganism inactivation, UV disinfection was also capable of degrading micropollutants such as carbamazepine with the assistance of ubiquitous nitrate in wastewater. 31 Increasing studies have reported that the constructed wetland could effectively attenuate excess nutrients and remove micropollutants.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DB is considered as a tertiary technology for further purifying nitrate-rich wastewater and has been widely applied in full-scale WWTPs. 30 In addition to microorganism inactivation, UV disinfection was also capable of degrading micropollutants such as carbamazepine with the assistance of ubiquitous nitrate in wastewater. 31 Increasing studies have reported that the constructed wetland could effectively attenuate excess nutrients and remove micropollutants.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Emerging pollutants and increasing demand for clean water simultaneously call for municipal TWTPs, such as DB, disinfection and constructed wetland. DB is considered as a tertiary technology for further purifying nitrate-rich wastewater and has been widely applied in full-scale WWTPs . In addition to microorganism inactivation, UV disinfection was also capable of degrading micropollutants such as carbamazepine with the assistance of ubiquitous nitrate in wastewater .…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of lines indicates the number of processes within a given category (e.g., biological processes or biological nitrogen processes), and the size of points indicates the number of processes within a given process group (e.g., microbial fuel cell). A full list of processes, as well as classification into process groups and by core attributes, is included in Table S3-1. ...…”
Section: State Of the Artmentioning
confidence: 99%
“…However, the rural sewage, with a low C/N ratio (3:1-5:1), cannot satisfy the carbon source demand of denitrifying microorganisms in the ISTY, thus affecting the nitrogen removal efficiency of the ISTY. Given insufficient influent carbon source, high-quality carbon source, such as glucose, lactose, methanol, and acetic acid, is added to improve the sewage C/N [1,2]. However, adding high-quality carbon sources has some disadvantages, such as high cost and inconvenient transportation [3][4][5], and produces excessive sludge in the treatment system.…”
Section: Introductionmentioning
confidence: 99%